2022
DOI: 10.1242/dmm.049615
|View full text |Cite
|
Sign up to set email alerts
|

Consensus guidelines on the construct validity of rodent models of restless legs syndrome

Abstract: Our understanding of the causes and natural course of restless legs syndrome (RLS) is incomplete. The lack of objective diagnostic biomarkers remains a challenge for clinical research and for the development of valid animal models. As a task force of preclinical and clinical scientists, we have previously defined face validity parameters for rodent models of RLS. In this article, we establish new guidelines for the construct validity of RLS rodent models. To do so, we first determined and agreed on the risk, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 159 publications
0
3
0
Order By: Relevance
“…BID in rodents is a well-accepted animal model of RLS, which can be induced by providing a severe iron-deficient diet during the postweaning period. The model has both construct and face validity since it recapitulates several biochemical and behavioral findings of RLS ( 109 , 110 ). Using the optogenetic-microdialysis method, an increase in the sensitivity of cortico-striatal terminals to release glutamate could be demonstrated in the rat with BID, since a lower frequency of optogenetic stimulation was necessary to induce striatal glutamate release as compared to controls ( 55 ).…”
Section: D 4 R Agonists As Plausible Treatment Of ...mentioning
confidence: 86%
“…BID in rodents is a well-accepted animal model of RLS, which can be induced by providing a severe iron-deficient diet during the postweaning period. The model has both construct and face validity since it recapitulates several biochemical and behavioral findings of RLS ( 109 , 110 ). Using the optogenetic-microdialysis method, an increase in the sensitivity of cortico-striatal terminals to release glutamate could be demonstrated in the rat with BID, since a lower frequency of optogenetic stimulation was necessary to induce striatal glutamate release as compared to controls ( 55 ).…”
Section: D 4 R Agonists As Plausible Treatment Of ...mentioning
confidence: 86%
“…In addition to the future directions listed throughout the review, other directions are worth exploring. For example, animal models of RLS have targeted iron deficiency, the dopaminergic system [ 111 112 113 ] as well as the endogenous opiate system [ 83 84 85 ]. Vitamin D deficiency models have been created, but to our knowledge the clinical or biochemical particularities of RLS have not been investigated in these models [ 114 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…RLS is a multifaceted neurological disorder with a wide range of both genetic and non-genetic components. The interplay between these different factors makes it difficult to identify a singular animal model that combines face validity with construct validity ( 52 , 53 ). Several risk genes have been identified in genome-wide association studies, and the mutation of these risk gene orthologs in mice showed phenotypes relevant to RLS, such as alterations in iron metabolism, dopamine function, sensory perception, and sleep [e.g., MEIS1: ( 33 , 54 , 55 ); BTBD9: ( 56–58 ); PTPRD: ( 18 ); D3KO: ( 30 , 33 , 59 , 60 )].…”
Section: Discussionmentioning
confidence: 99%